2018
DOI: 10.1186/s12992-018-0382-5
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and awareness of medical assistance while traveling abroad

Abstract: BackgroundWith globalization, more and more people travel to countries where they are at risk of injuries and travel-related diseases. To protect travelers’ health, it is crucial to understand whether travelers accurately perceive medical assistance resources before and during their trips. This study investigated the need, awareness, and previous usage of overseas emergency medical assistance services (EMAS) among people traveling abroad.MethodsAnonymous questionnaires were distributed to patients (n = 500) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
3
2
Order By: Relevance
“…Among the respondents, 19.2% of subjects reported previous travel-associated illness. Compared with previous studies, about 14.2-60% of travelers experienced health problems during travel [10,12,13], the reason for the relatively low proportion in this study might be due to the younger age and higher educational level of our respondents. There were 39.7% of our subjects aged 20-30 years and 79.2% of our subjects were graduated from university or higher.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Among the respondents, 19.2% of subjects reported previous travel-associated illness. Compared with previous studies, about 14.2-60% of travelers experienced health problems during travel [10,12,13], the reason for the relatively low proportion in this study might be due to the younger age and higher educational level of our respondents. There were 39.7% of our subjects aged 20-30 years and 79.2% of our subjects were graduated from university or higher.…”
Section: Discussioncontrasting
confidence: 89%
“…Christopher et al revealed only 36% people sought pre-travel counseling [16]. The pre-travel consultation rate was 0.1% in Taiwan while was 40.5% for all ill GoeSentinel travelers [10]. Although the percentage of willing for pre-travel consultation was low, the percentage of willing to buy travel related insurance was about 60-80% in this study.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Indeed, emergency medical assistance service (EMAS) was perceived to be fundamental by international travellers based on a recent survey. 49 The study did not exclusively include travellers with CVD. Importantly, about 30% of travellers were not aware of EMAS abroad.…”
Section: Travel Insurancementioning
confidence: 99%
“…Recent studies have shown that approximately 60% of General Practitioners in New Zealand [ 7 ] and 39% of travel clinics worldwide [ 8 ] usually advise travelers to buy travel insurance. Furthermore, as our previous study has shown, overseas emergency medical assistance services (EMAS) were considered important to travelers, but approximately 20%–30% of travelers lacked awareness about EMAS [ 9 ]. Since travel medicine services have also been indispensable in the COVID-19 pandemic, we realized that pre-travel healthcare will be even more vital in the future [ 10 ].…”
Section: Introductionmentioning
confidence: 99%